Scintillation properties of Eu²⁺-doped SrCl₂ and CsSrCl₃ single crystals - Cherginets, V.L.; Grippa, A.Yu.; Rebrova, T.P.; Datsko, Yu.N.; Ponomarenko, T.V.; Rebrova, N.V.; Kosinov, N.N.; Tarasenko, O.A.; Dolzhenko, Yu.I.; Zelenskaya, O.V. (Functional Materials, 2012)
Eu²⁺-doped CsSrCl₃ scintillation crystals with activator concentration 0.5, 1 and 5 mol. % and SrCl₂: Eu²⁺ material doped with 1 mol. % of the activator have been grown by Bridg-man-Stockbarger method. The radioluminescence spectra of CsSrCl₃: Eu²⁺ materials include a narrow band with the maximum which position is shifted from 437 to 448 nm with Eu²⁺ concentration increase and the spectrum for SrCl₂:Eu²⁺ contains a band with the maximum at 414 nm. The light yield of CsSrCl₃:Eu²⁺ material achieves maximal value at 5 mol. % of Eu²⁺ and it is equal to 39 % in respect to Nal:TI (ca 16,000 photons per MeV) and energetic resolution R is 11.5 %, whereas for SrCl₂:l mol. % of Eu²⁺ the light yield consists 30 % (ca 12,000 photons per MeV) and R = 9.2 %. The scintillation pulse decay curves for CsSrCl₃:Eu²⁺ is described by two components with the decay constants 420 ns and 2.8 ps and the fraction of the faster component is 0.3.